412 Combination of Genomic Technologies and Consanguinity in Order to Identify Pathogenic Variants in Recessive Disorders. (October 2012) - Makrythanasis, P; Nelis, M; Santoni, FA; Guipponi, M; Béna, F; Vanier, A; Duriaux-Sail, G; Gimelli, S; Stathaki, E; Falconnet, E; Temtamy, S; Megarbane, A; et al.
Abstract : Consanguinity and inbreeding increase the sharing of alleles among individuals; thus a considerable number of autosomal recessive phenotypes occur in offspring(s) of consanguineous couples. We have collected samples from consanguineous families with different phenotypes of unknown etiology that are compatible with autosomal recessive transmission, in order to identify the responsible functional genomic variation. 42 families of different ethnic background have been collected so far. From each family, DNA from the patient(s), unaffected siblings and the parents is extracted. Samples are i/analyzed by array-CGH for the detection of homozygous deletions; ii/genotyped with a 720K SNP-array in order to identify Runs of Homozygosity and the areas of the genome that could include the causative variant; iii/exome sequenced (one affected individual/family). Mean coverage is 130x and 98.2% of the coding region of RefSeq is covered at least 8x. By comparing the genotyping and sequencing data, we found that Single Nucleotide Variants (that passed the quality threshold) were detected with a specificity of 99.95%, sensitivity of 97.7%, Positive Predictive Value 99.2% and Negative Predictive Value 98.6%. On average we identified 21901 variants/exome. So far we analysed 26 families and identified the causative variation in known genes in 3 of them:VLDLR, FKTN and DMP1. In 12 families 23 candidate genes/variants have been identified(more than 1 candidate genes/family). In 11 families the likely molecular defect has not been identified. Consanguineous families provide an opportunity to identify pathogenic variants responsible for recessive phenotypes and rapidly fill in the gap between genotype and phenotype.